COVID-19 distance learning of english as a second language - Marjana Vaneva; Vladica Maleska (University American College Skopje, 2021)
This study investigates distance learning of English as a second language in primary and secondary schools in the Republic of N. Macedonia during the COVID-19 pandemic, which started in March 2020 when the government of our country, like everywhere else, decided to close the schools in order to protect student's health. The aim of the study is to define distance learning as a concept, and elaborate on the four main pillars or aspects of distance learning in general and of English language learning, specifically: technological pillars or infrastructure, human resources, the design of the teaching system and pedagogical and social dimension. Data and information for all four aspects have been collected from primary and secondary resources and analyzed accordingly. Questionnaires and interviews have been used as tools to give us insight into the research problem. The findings have shown that both teachers and students find distance learning quite challenging. Although it is functioning well, there are certain barriers to overcome and better methods for learning to be found. The study recommends that the country should help more by providing funding for better learning platforms, and to help and support school teachers. Distance learning is the only alternative in the COVID-19 pandemic, but all stakeholders (ESL teachers, pupils, parents and experts) included in our interviews, agree that language is acquired through interaction, that language development is a social construct and pupils need to have lots of peer interaction.
Keywords: 330; English as a second language; distance learning; mediated learning; COVID-19 pandemic; distance education; pillars of distance learning; design of the teaching system; learning platforms